A Flowering Locus C Homolog Is a Vernalization-Regulated Repressor in Brachypodium and Is Cold Regulated in Wheat. Issue 2 (29th December 2016) - Sharma, Neha; Ruelens, Philip; D'hauw, Mariëlla; Maggen, Thomas; Dochy, Niklas; Torfs, Sanne; Kaufmann, Kerstin; Rohde, Antje; Geuten, Koen
Abstract : ODDSOC2/TaAGL33 functions in vernalization-responsive flowering of Poaceae in a similar but unique manner compared to its Arabidopsis homolog, FLOWERING LOCUS C. Abstract: Winter cereals require prolonged cold to transition from vegetative to reproductive development. This process, referred to as vernalization, has been extensively studied in Arabidopsis ( Arabidopsis thaliana ). In Arabidopsis, a key flowering repressor called FLOWERING LOCUS C ( FLC ) quantitatively controls the vernalization requirement. By contrast, in cereals, the vernalization response is mainly regulated by the VERNALIZATION genes, VRN1 and VRN2 . Here, we characterize ODDSOC2, a recently identified FLC ortholog in monocots, knowing that it belongs to the FLC lineage. By studying its expression in a diverse set of Brachypodium accessions, we find that it is a good predictor of the vernalization requirement. Analyses of transgenics demonstrated that BdODDSOC2 functions as a vernalization-regulated flowering repressor. In most Brachypodium accessions BdODDSOC2 is down-regulated by cold, and in one of the winter accessions in which this down-regulation was evident, BdODDSOC2 responded to cold before BdVRN1. When stably down-regulated, the mechanism is associated with spreading H3K27me3 modifications at the BdODDSOC2 chromatin. Finally, homoeolog-specific gene expression analyses identify TaAGL33 and its splice variant TaAGL22 as the FLC orthologs in wheat ( Triticum aestivum ) behaving most similar to Brachypodium ODDSOC2 . Overall, our study suggests that ODDSOC2 is not only phylogenetically related to FLC in eudicots but also functions as a flowering repressor in the vernalization pathway of Brachypodium and likely other temperate grasses. These insights could prove useful in breeding efforts to refine the vernalization requirement of temperate cereals and adapt varieties to changing climates.